The Internalization of Islamic Moderate Values in the book of Tarjuman by KH. Abdul Hamid Bin Isbat: Case Study At-Mujtama’ Boarding School - Samsul Ar (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
In Islamic teachings, being moderate will give birth to peace. In other words, moderation in everyday life is very important and very necessary to promote an attitude of tolerance and differences. As in Indonesia, we have various tribes, religions, and languages, and we must be tolerant of every religious teaching and the diversity of tribes there.This study examines the internalization of moderate values in the Tarjuman book by KH. Abdul Hamid bin Isbat at Al-Mujtama’ Islamic Boarding School, Pamekasan. The Tarjuman book contains Islamic values that emphasize religious moderation, aligning with Thomas Lickona’s concept of character education. This research employs a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation within the pesantren environment. The findings indicate that the internalization of moderate values in the Tarjuman book is implemented through three stages. First, moral knowing where students are provided with an understanding of moderation concepts through book studies. Second, moral feeling which is developed through discussions, spiritual experiences, and the exemplary conduct of kiai in daily life. Third, moral action is manifested in attitudes of tolerance, respect for differences, and the application of moderate values in social interactions. The results of this study affirm that pesantren education plays a strategic role in shaping students’ moderate character. Moreover, the Tarjuman book functions not only as an Islamic reference but also as an instrument for character development, fostering a balanced approach to religion and social life.